EFEKTIFITAS PREPARASI KULIT MENGGUNAKAN KLORHEXIDIN 7,5% SETRIMID 15%-POVIDON IODIN 10% DAN POVIDON IODIN 10%-ALKOHOL 70% TERHADAP INFEKSI LUKA OPERASI SEKSIO SESAREA DI RSUD DR. HARYOTO LUMAJANG (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Surgical wound infections are the second most common cause of nosocomial infections and have high morbidity and mortality rates. The use of antiseptic skin preparations is effective in preventing surgical wound infections. There is still insufficient evidence to evaluate the type, concentration and method of use of antiseptic agents for skin preparation in cesarean section. The aim of the study was to determine the effectiveness of skin preparation using chlorhexidine 7.5%, cetrimide 15%-povidone iodine 10% and povidone iodine 10%-alcohol 70% against Wound Infections for Caesarean Section Operations in RSUD Dr. Haryoto Lumajang. The research design used is quantitative research with a quasi-experimental approach, post test only-control group design. The population in this study were patients who underwent cesarean section at RSUD Dr. Haryoto Lumajangl. The sample was selected by accidental sampling from 27 February 2023 to 25 March 2023, and 66 respondents were found who met the inclusion and exclusion criteria. The samples were divided into 2 groups: the test group (33 samples) received a combination skin preparation of 7.5% chlorhexidine, setrimide 15% - 10% povidone iodine and the control group (33 samples) received a skin preparation combination of 10% povidone iodine - 70% alcohol . Observation of the surgical wound was carried out on day 3 and day 10. The results of this study indicated that there was no incidence of surgical wound infection on the third day. Surgical wound infections on the 10th day in the 7.5% chlorhexidine skin preparation group, setrimide 15% - 10% povidone iodine by 2 respondents and in the 10% povidone iodine skin preparation group - alcohol by 4 respondents. But statistically it was not significantly different from the value of p = 0.395, meaning that Ho was accepted and Ha was rejected, so there was no significant difference between skin preparation using chlorhexidine 7.5% setrimide 15% - 10% povidone iodine and 10% povidone iodine - 70% alcohol on the Incidence of Wound Infection by Caesarean Section at RSUD Dr. Haryoto Lumajang. With the difference in the incidence of surgical wound infection, it can be considered and an alternative for Dr. Haryoto Lumajang to use skin preparation using 7.5% chlorhexidine, 15% setrimide-10% povidone iodine Keywords: Surgical wound infection, skin preparation, chlorhexidine, povidone iodine, alcohol, cesarean section.